Penyuluhan Pengembangan Produk Kreatif untuk Mendukung UMKM di Kelurahan Maleer Kota Bandung - Yuniarty, Neneng; Trimastuti, Wahyu; Triswastika, Arimbi; Insani, Siti; Legistari, Kartika; Christinawati, Santy (PADMA, 2024)
The counseling on the development of creative products to support MSMEs in Maleer Village, Bandung City, aims to enhance the capacity of MSME actors in creating innovative products with high competitiveness. This activity focuses on understanding the importance of creativity in product development as well as the implementation of effective marketing strategies, utilizing technology and digital platforms. Through this counseling, MSME actors are provided with knowledge and skills in product design, efficient use of raw materials, and how to utilize social media and e-commerce to expand their market reach. Additionally, the training emphasizes the importance of good business management, including financial management and branding, so that the products produced can compete in both local and global markets. With this counseling, it is expected that MSMEs in Maleer Village can develop better, strengthen local economic competitiveness, and contribute positively to the economy of Bandung City. Of the 50 participants, 15 (30%) fully understood, 10 (20%) had a moderate understanding, and 25 (50%) understood the material.